Argumentative Interaction as a Tool to Promote Critical Thinking in Educational Contexts (Docentes 2.0 Journal, 2026)
Argumentative interaction is a fundamental factor in contemporary education. The objective was to analyze argumentative practices in an educational institution, understand their application in the classroom, and identify the reasons teachers integrate them into their teaching sequences. The research was framed within the interpretive paradigm, using a case study method and a qualitative approach, with a descriptive, cross-sectional design. The natural observation technique was used in a private educational institution in Cusco, Peru, with 22 high school seniors and three teachers. Through observational records, three types of practices were identified: proto-argumentative, type 1 argumentative, and type 2 argumentative. Proto-argumentative practices show points of view without a formal reasoning structure. At the same time, the dynamics promoted by the teacher distinguish type 1 and type 2 argumentative practices, the reasoning developed, and the questions asked. Within type 1 practices, subcategories were identified according to the pedagogical objective, and levels of increasing complexity in interactions were established. This analysis provided an understanding of how argumentative practices contribute to critical thinking and offer tools for designing effective pedagogical strategies.
Keywords: Critical thinking; Argument; Reasoning